EFFECTIVENESS OF EFFLEURAGE MASSAGE ON REDUCING INTENSITY OF FIRST-STAGE INPARTUM PAIN - Puspitasari, R.A. Helda; Kusuma, Erik; Handayani, Dwining; Dewi Nastiti, Ayu; Toha, Muhammad; Ayu Novitasari, Bunga (Universitas Airlangga, 2024)
Introduction: Labor can be defined as the process of opening and thinning the cervix, as well as the descent of the fetus into the birth canal. This pain can be felt like strong cramps in the stomach, groin, and back, as well as aches (Rosmiarti et al., 2020). In general, the pain that arises can affect the physiological and psychological state of the mother in the form of intense fatigue, the emergence of fear and worry, and cause stress, thus making a lack of contractions which can cause prolonged labor. The purpose of this literature review is to find out and analyze the effectiveness of effleurage massage in reducing the intensity of labor pain in the first stage. Methods: This study uses a literature review method with article searches conducted in three search databases Science Direct, Garuda, Google Scholar and there are 10 articles that meet all inclusion criteria and are reviewed. Results: Effleurage massage can reduce the intensity of labor pain in the 1st stage. Conclusion: Based on the results of a review of 10 articles, one of the non-pharmacological therapies to reduce the intensity of labor pain is using effleurage massage therapy. This is evidenced by the average headache scale before being treated with effleurage massage which is on the moderate pain scale (4-6). After being treated with effleurage massage, the pain intensity was on a mild pain scale (1-3). Effleurage massage therapy is also able to reduce the scale of severe pain (7-10) to mild pain (0-3).